The essential Jesus. ([Kingsford, N.S.W.] : Matthias media, 2008)
".. the story of the most extraordinary and influential man ever to have walked on this planet - Jesus of Nazareth. The biography or 'Gospel' of Jesus' life was written nearly 2000 years ago by a doctor named Luke. It's been speaking to people of every background, race and situation ever since."
Keywords: Jesus Christ -- Biography; Jesus Christ -- Biography